Ulinastatin administration is associated with a lower incidence of acute kidney injury after cardiac surgery: a propensity score matched study - Wan, Xin (Crit Care, 2016)
BACKGROUND: Systemic inflammation is involved in the development of acute kidney injury (AKI) after cardiac surgery with cardiopulmonary bypass (CPB). Ulinastatin, a urinary trypsin inhibitor (UTI), possesses a variety of anti-inflammatory effects. Therefore, we hypothesized that the administration of ulinastatin would reduce the occurrence of AKI in patients undergoing cardiac surgery with CPB. METHODS: A retrospective propensity score matched analysis was used to evaluate the effect of ulinastatin on the development of AKI in patients undergoing first documented cardiac surgery with CPB between January 2008 and December 2012 in our hospital. Multiple logistic regression models were also employed to identify the association between UTI administration and development of AKI. RESULTS: A total of 2072 patients who underwent cardiac surgery with CPB met the inclusion criteria. Before propensity score matching, variables such as age, baseline creatinine, CPB duration, red blood cells transfused, and hematocrit were statistically different between the ulinastatin (UTI) group and the control group. On the basis of propensity scores, 409 UTI patients were successfully matched to the 409 patients from among those 1663 patients without UTI administration. After propensity score matching, no statistically significant differences in the baseline characteristics were found between the UTI group and the control group. The propensity score matched cohort analysis revealed that AKI and the need for renal replacement therapy occurred more frequently in the control group than in the UTI group (40.83 % vs. 30.32 %, P = 0.002; 2.44 % vs. 0.49 %, P = 0.02, respectively). However, there were no significant differences in mortality, length of intensive care unit stay, and length of hospital stay between the UTI group and the control group. Using multivariate logistic regression analysis, we found ulinastatin played a protective role in the development of AKI after cardiac surgery (odds ratio 0.71, 95 % confidence interval 0.56–0.90, P = 0.005). CONCLUSIONS: This study shows that ulinastatin was associated with a lower incidence of AKI after cardiac surgery, suggesting that the administration of ulinastatin may be favorable for those patients undergoing cardiac surgery with CPB.